Pengaruh Pengetahuan, Sikap, Persepsi, Rekan kerja, dan Penghasilan Terhadap Perilaku Safety Riding Pengemudi Ojek Menara Sunan Kudus - Surya Atmaja, Fajar; Sugianto, Sugianto; Basuki, Ahmad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
This research aims to examine the influence of knowledge, attitudes, perceptions, co-workers, and income on the safety riding behavior of motorbike taxi drivers at Menara Sunan Kudus. Considering the high risk of accidents faced by motorcycle taxi drivers, understanding the factors that influence safe driving behavior is very important. This research uses a quantitative approach with a survey method of 100 motorcycle taxi drivers. Data were collected through questionnaires designed to measure safety knowledge, attitudes toward safety, risk perception, co-worker influence, and income level. Data analysis was carried out using multiple linear regression to determine the influence of each independent variable on safety riding behavior. The results of the analysis show that safety knowledge, attitudes towards safety, and risk perception have a significant positive influence on safety riding behavior. Apart from that, the influence of co-workers and income did not show a significant influence on safety riding behavior. These findings provide important insights for the development of more effective training programs and safety campaigns, with an emphasis on improving safety knowledge and attitudes and strengthening the positive influence of drivers' risk perceptions. Thus, efforts to improve driving safety among motorcycle taxi drivers can be focused on aspects that are proven to significantly influence safety riding behavior.